Disintegration: Dynamics and Polemics of Umayyad and Abbasid Leadership - Santi Nirmala Dewi; Siti Sofiah Al-Adawiyah; Imam Tabroni; Elladdadi Mark; Amina Intes (International Journal of Educational Narratives, 2023)
Background. The Umayyad dynasty was the beginning of absolute monarchy in the Islamic concept of government. Muawiyah as the founder of the dynasty actually adopted from the two previous great empires of Byzatium and Persia. Purpose. The aim of the Umayyad rule was to develop science. At the end of the Umayyad rule, around the seventh century, there were a number of revolts throughout the country. Method. The writing of this article uses the manuscript review method, in this writing is the Disintegration of the Umayyad Dynasty and the Abbasid Dynasty in the Years 1000 - 1250 AD. the source used is secondary data where the author uses literature obtained from literature studies to several journals, books, and trusted articles. Writing with a study of several sources of books or journals is intended to get more complex data to make one complete writing. Results. In the first period, the Abbasid dynasty faced many challenges and disturbances. Several political movements that undermined the government and destabilized it appeared everywhere, both internal movements of the Abbas family itself and from outside. Conclusion. The situation of the Abbasid dynasty before the disintegration was relatively stable, the situation was seen that all the problems faced in the early period could be resolved properly. It is even famous in history that the first period of the Abbasid dynasty was a period of progress, where all lines of life experienced rapid progress.